EviSIP: using evidence to change practice through mentorship - an innovative experience for reproductive health in the Latin American and Caribbean regions - Suzanne J. Serruya; Rodolfo Gómez Ponce de León; Maria V. Bahamondes; Bremen De Mucio; Maria L. Costa; Pablo Durán; José L. Díaz-Rosello; Caron Kim; Antonella F. Lavelanet; Ana Artigas; Thais A. Forster; José G. Cecatti (Taylor & Francis Group, 2020)
Maternal mortality is unacceptably high in our region. In 2015, the Latin American Center for Perinatology and Women´s Reproductive Health (CLAP) created a regional network of institutions including 16 countries, committed to improving epidemiological surveillance and healthcare of women in a situation of abortion or near miss event, using a common platform, the Perinatal Information System (SIP). The objective of the current pilot project was to test a new method of study called EviSIP (Evidence from SIP), a method of generating information on maternal near miss and abortion for the region. We describe the implementation of this initiative in reproductive healthcare facilities using SIP. Junior researchers/clinicians from these countries were included, along with expert researchers in reproductive health from across the world. Articles were produced with data on maternal near miss and abortion gathered from the SIP of each participating sentinel center; and recommendations from experts. EviSIP was the first joint workspace to discuss patient outcomes after treatment of abortion or near miss cases, with data analysis of each Sentinel Center; discuss and analyze data among centers, at a country and regional level; discuss the main outcomes and their impact on changing procedures and policies; strengthen the operational research capacity of the centers; develop and encourage the publication of scientific articles. The EviSIP initiative also promoted training of healthcare professionals in research. EviSIP provided a unique opportunity to train for research and mentorship and was pivotal to the production of scientific knowledge of reproductive health in the region.